Cubic phase nanoparticles for sustained release of ibuprofen: formulation, characterization, and enhanced bioavailability study - Dian, Linghui (Dove Medical Press, 2013)
In order to improve the oral bioavailability of ibuprofen, ibuprofen-loaded cubic nanoparticles were prepared as a delivery system for aqueous formulations. The cubic inner structure was verified by cryogenic transmission electron microscopy. With an encapsulation efficiency greater than 85%, the ibuprofen-loaded cubic nanoparticles had a narrow size distribution around a mean size of 238 nm. Differential scanning calorimetry and X-ray diffraction determined that ibuprofen was in an amorphous and molecular form within the lipid matrix. The in vitro release of ibuprofen from cubic nanoparticles was greater than 80% at 24 hours, showing sustained characteristics. The pharmacokinetic study in beagle dogs showed improved absorption of ibuprofen from cubic nanoparticles compared to that of pure ibuprofen, with evidence of a longer half-life and a relative oral bioavailability of 222% (P < 0.05). The ibuprofen-loaded cubic nanoparticles provide a promising carrier candidate with an efficient drug delivery for therapeutic treatment.